PENGARUH PENAMBAHAN SERAT KULIT PINANG DAN SERBUK KAYU TERHADAP KUAT TARIK BELAH BETON (Kajian Terhadap Ukuran Agregat Maksimal 10 mm) - Hasanah, Era Rizky; Gunawan, Agustin; Afrizal, Yuzuar (Universitas Bengkulu, 2017)
Concrete has a high compressive strength, but it is low to tensile strength. The pinang skin fiber and wood powderuse to increase the tensile strength. The purpose of this research is to know the effect of addition toward tensile strength and addition percentage variation in concrete that will get the highest tensile strength.The cylindrical specimens with size of 30 cm high and 15 cm diameter to 20 specimens, they are 4 sample of normal concrete and 16 sample of variation oncrete. The addition of pinang skin fiber and wood powder with variation of 0.25%, 0.5%, 0.75%, and 1% of the weight volume of the specimen with used 50% pinang skin fiber and 50% wood powder.The mixture of concrete uses water cement ratioof 0.5 and 60-100 mm slump.The test specimen is immersed for 26 days and the concrete tensile strength test conducted after the concrete at 28 days adding 7 days for drying.The result of this research shows that the variation concrete of 0.25% and 0.5% have increased of tensile strength than the normal concrete as 12.272% and 4.369%. Beside that for the variation concrete of 0.75% and 1% have decreased as 5.044% and 11.929%. The increase of tensile strength value of optimal concrete is found in variation 0.25% that is 12.272% from normal concrete.